Influencing factors and predictions of carbon emissions for the chemical industry in China - Wang, Weiru; Hu, Fan; Li, Mengzan; Shi, Xincong; Liu, Xinyuan (Frontiers in Energy Research, 2024)
As global warming increases the frequent occurrences of natural disasters, the reduction of carbon emission has become a hot issue around the world. The chemical industry is an import source of carbon emission in China. The carbon emission of chemical industry is calculated from the year 2000 to 2019 by using emission factor method. The logarithmic mean divisia index (LMDI) method is exploited to analyze the influencing factors of carbon emission, and the variations of carbon emission are attributed to the contributions of carbon intensity, energy structure, energy intensity, industrial value-added rate, per capita industrial output value and industrial scale. The results of decomposition shows that per capita industrial output value is the main driving factor and energy intensity is main inhibiting factor of chemical industry's carbon emission. In order to quantify the variation of carbon emissions, the extended stochastic impacts by regression on population, affluence and technology (STIRPAT) model is constructed and examined. Using the STIRPAT model, the basic scenario and energy intensity control scenario are set and the carbon emissions are predicted, which shows that under strict energy intensity control scenario carbon emissions may reach peak around the year 2031.The influencing factors of decomposition and prediction of carbon emission should be helpful for carbon emission reduction of chemical industry in China.As the largest developing country, the rapid development of economy has brought about huge carbon emissions in China. In order to effectively reduce carbon emissions, the Chinese government hopes to realize carbon peaking in 2030 and carbon neutrality in 2060. Thus, China faces huge pressure on reduction of carbon emissions. The analysis and prediction of carbon emissions is of great significance for controlling the total amount and intensity of carbon emissions in China.From a macro perspective, some industries such as electric power, construction and chemical industry are the main sources of carbon emissions in China. The researches on carbon emission and e 删除[作者]: